Sport and the Pandemic. Perspectives on Covid-19's Impact on the Sport Industry (Sport and the Pandemic. Perspectives on Covid-19's Impact on the Sport Industry, 2020)
This book takes a close look at how the sport industry has been impacted by the global Coronavirus pandemic, as entire seasons have been cut short, events have been cancelled, athletes have been infected, and sport studies programs have moved online. Crucially, the book also asks how the industry might move forward.